Evolution of pore structure and fractal characteristics during hydrate-based CO2 sequestration in unconsolidated sediments - Zhun Zhang; Yuning Liu; Yunkai Ji; Jiaxian Wang; JinQiu Hu; Bin Fang; Wanjun Lu; Changling Liu; Fulong Ning (Chemical Engineering Journal, 2026)

Multi-omics combined with simulated fermentation model for elucidation of variation patterns of lipids and volatiles and its mechanism during black tea fermentation - Linchi Niu; Yuning Feng; Shan Zhang; Zhizhen Fang; Rui Liang; Zhenxing Xu; Xujiang Shan; Qinghua Zhou; Haibo Yuan; Yongwen Jiang; Jia Li (Food Chemistry, 2026)

Lipid profiles and metabolic characteristics of Chinese tea cultivars (Camellia sinensis) with different manufacturing suitabilities by comparative lipidomics using UHPLC-Q-Exactive mass spectrometry - Le Chen; Jianqiang Ma; Linchi Niu; Yuning Feng; Zhizhen Fang; Shan Zhang; Xujiang Shan; Qianting Zhang; Qinghua Zhou; Yongwen Jiang; Haibo Yuan; Jia Li (Food Chemistry, 2025)

Quantitative non-volatile sensometabolome of Longjing tea and discrimination of taste quality by sensory analysis, large-scale quantitative metabolomics and machine learning - Xujiang Shan; Linchi Niu; Qianting Zhang; Zhizhen Fang; Yuning Feng; Rui Liang; Zhenxing Xu; Shan Zhang; Le Chen; Weidong Dai; Qinghua Zhou; Yongwen Jiang; et al. (Food Chemistry, 2025)

Insight into homogeneous activation of sodium hypochlorite by dithionite coupled with dissolved oxygen (DO@NaClO/DTN) for carbamazepine degradation - Wei Song; Hongze Fang; Zhaosheng Lei; Ruigang Wang; Caixia Fu; Fei Wang; Yuning Fang; Xing Du; Zhihong Wang; Zhiwei Zhao (Water Research, 2025)

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Polyvinylimidazolium/polyacrylonitrile nanofiber separator with enhanced polysulfide adsorption toward durable lithium–sulfur batteries - Ping Feng; Chenxiao Lin; Fang Chen; Yiwei Gao; Yuning Fang; Yong Zheng; Yan Yan; Mingkai Liu (Chemical Engineering Journal, 2025)

Synergistically enhanced heterogeneous activation of dissolved oxygen for aqueous carbamazepine degradation over S(III) coupled with siderite - Yuning Fang; Fei Wang; Hongze Fang; Zhaosheng Lei; Wei Song; Caixia Fu; Xing Du; Zhihong Wang; Zhiwei Zhao (Environmental Pollution, 2024)

Degradation of sulfamethazine in coastal aquaculture tailwater by Na2S2O4@iron-electrode electrooxidation combined with ceramic membrane process - Wei Song; Yuning Fang; Hongze Fang; Deming Gu; Xing Du; Sen Xu; Caixia Fu; Yu Zhou; Zhihong Wang (Environmental Pollution, 2024)

Designing and fabricating a neoteric immobilized Z-scheme V2O5/FeVO4/430-stainless steel foil photocatalyst composite film for tetracycline degradation with synchronous hydrogen production - Yuning Tu; Ying Liu; Shengwei Chi; Ying Tian; Jiaqi Dang; Taiyu Jin; Dawei Fang; Jun Wang (Journal of Environmental Chemical Engineering, 2024)

Research on the Spatial Differentiation Characteristics and Sustainable Development of UGGp in China - Xia Li; Qingcheng He; Bo Xing; Jin Wu; Yuning Ding; Fang Ren; Yi Ding (Geoheritage, 2023)

Occurrence of halogenated methanesulfonic acids in water and sediment from the Hangzhou Bay, China - Fang Tao; Yujia Tan; Junwei Dai; Congrui Lu; Yadong Sha; Yi Liu; Xinxing Zhou; Qingele Hasi; Zhemin Shen; Yuning Ma (Environmental Research, 2023)

Single and combined toxicity assessment of primary or UV-aged microplastics and adsorbed organic pollutants on microalga Chlorella pyrenoidosa - Wei Song; Caixia Fu; Yuning Fang; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Kalpana Bhatt; Lu Liu; Ningjie Wang; Fang Liu; Shunni Zhu (Environmental Pollution, 2023)

Stitching electron localized heptazine units with “carbon patches” to regulate exciton dissociation behavior of carbon nitride for photocatalytic elimination of petroleum hydrocarbons - Qi Guo; Yuning Wu; Linhong Xia; Xue-Fang Yu; Kaisheng Zhang; Yujie Du; Lixue Zhang; Hua Tang; Jianbo Cheng; Jianpeng Shang; Yanhua Peng; Zhuo Li; et al. (Chemical Engineering Journal, 2023)

Soil Aggregation in Relation to Organic Amendment: a Synthesis - Tushar C. Sarker; Maurizio Zotti; Yuning Fang; Francesco Giannino; Stefano Mazzoleni; Giuliano Bonanomi; Yanjiang Cai; Scott X. Chang (Journal of Soil Science and Plant Nutrition, 2022)

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Reduced glycodeoxycholic acid levels are associated with negative clinical outcomes of gestational diabetes mellitus - Bo Zhu; Zhixin Ma; Yuning Zhu; Lei Fang; Hong Zhang; Hongwei Kong; Dajing Xia (Journal of Zhejiang University-SCIENCE B, 2021)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)